Genotypic variability for root nodulation and identification of high yielding chickpea (Cicer arietinum L.) genotypes - Jyoti Kumari, Rafat Sultana*, Zafar Imam, Mankesh Kumar and Reena Kumari (Electronic Journal of Plant Breeding)
Evaluating diverse chickpea genotypes for growth, root nodule, and yield parameters can provide valuable insights to identify genotypes with desirable traits for improved crop production. The investigation on root nodule parameters can shed light on the nodulation potential and nitrogen-fixing efficiency of the genotypes and its role in enhancing grain yield as well as soil health. Hence, the present study was carried out involving 30 diverse chickpea genotypes including 3 checks and was evaluated under natural soil condition for agronomic traits associated with high root nodulation. Under natural soil condition (Sandy loam) chickpea nodule formation and nitrogen fixation ability were observed to vary significantly. The significant differences observed among the genotypes for all the parameters indicate the presence of genotypic variability. The flowering and pod formation stages demonstrated a significantly higher number of nodules per plant compared to other stages. Regarding the distribution of root nodules, it was found that the pre-flowering stage had the highest number of nodules on the primary roots. However, as the plant progressed into the later stages of flowering and podding, the nodules shifted to the secondary roots. Several traits have been found to correlate positively and significantly with seed yield. The genotypes namely BRHT-8, Sabour chana-2, BRHT-12, JG-218, ICC-67, BRHT-1, and BRHT-6 exhibited considerably high nodulation and seed yield/hectare.